Discourse Analysis of Speech Actions in Jihad Verses - Ebrahim Ebrahimi; Fatemeh Dastranj (پژوهش نامه معارف قرآنی, 2021)
The concept of war and jihad is one of the challenging researches, the misunderstanding of which has had negative consequences. Since in the verses of the Qur'an, the concept of jihad is a sacred and sublime thing and the Holy Qur'an has dealt with this issue in many verses and different interpretations, a correct analysis of the Qur'anic expression pattern and the way of using verbs can help to understand the verses of jihad. Therefore, in the present study, a descriptive-analytical method was used to analyze the discourse of spoken verbs in the verses of Jihad, and it was concluded that which is the intention of the speaker, a comprehensive combination of discourse systems derived from Verbal verbs, had an opinion. Hence, intelligent, emotional and incidental discourse systems that have been analyzed with regard to the spoken verbs of the verses of jihad, in combination with each other, clarify the comprehensive discourse analysis of the verses of jihad. This discourse is a guiding discourse that, in addition to intelligent discourse, uses tension-emotional pressures as well as event discourse based on divine providence. The emotional discourse system also completes the discourse of passion and consciousness in the form of emotional and persuasive speech verbs. The incidental discourse system in the form of obligatory verbal verbs refers to a higher and more meaningful authority and makes it clear that the divine providence is the victory and help of the Mujahideen in the way of God.